Efficacy and Safety of Avanafil in Chinese Subjects With Erectile Dysfunction: A Multi-Center, Randomized, Double-Blinded, Placebo-Controlled Phase III Clinical Trial. Issue 3 (5th March 2021) - Jiang, Hui; Lin, Haocheng; Li, Fubiao; Dai, Yutian; Zhang, Xiangsheng; Jiang, Tao; Deng, Junhong
Abstract: Introduction: The incidence of erectile dysfunction (ED) increases with age in mainland China and phosphodiesterase 5 inhibitors (PDE5i) are the major drugs used for its treatment. Aim: To determine the efficacy and safety of Chinese developed avanafil as therapy for ED in China. Methods: This phase III trial was carried out in 7 medical centers in China. Eligible subjects suffering from ED were allocated randomly into 3 groups (ratio 1:1:1) and orally received a placebo, 100 or 200 mg avanafil for a total of 12 weeks. Main Outcome Measures: The primary endpoint was changes in erectile function (EF) domain scores according to the International Index of EF (IIEF) questionnaire from baseline to week 12 of therapy. Secondary endpoints assessments were changes in the response rates of SEP, Q2 and Q3; changes in IIEF other domain scores. Safety evaluation monitored treatment-emergent adverse events (TEAEs), serious TEAEs, laboratory test results, vital signs and electrocardiographs. Results: Of 218 randomized ED subjects, 182 (83.5%) completed the study. After 12-week therapy, alterations from baseline of the mean IIEF-EF domain scores in the 100 mg and 200 mg groups were greater than for the placebo (all P < . 05) group. The changes in mean SEP Q2 response rates from baseline to week 12 in the placebo, 100 mg and 200 mg groups were 5.4%, 22.3% and 22.1%, and SEP Q3 response rate were 22.7%, 42.6% and 38.1%, respectively. Avanafil treatment (regardless of dose) improved EF vs placebo for most of other secondary efficacy endpoints studied (all P < . 05). No differences were detected in efficacy endpoints between the 100 and 200 mg dosage groups (all P > . 05) or in the incidence of TEAEs and drug-related TEAEs among the 3 groups (all P > . 05). Conclusion: Avanafil (100 or 200 mg) was effective and generally well tolerated in Chinese subjects with ED.